(untitled) (Bangladesh Journal of Botany, 2014)
Morphology and localization of the trichomes on vegetative and reproductive organs of Ajuga orientalis L. from Turkey were investigated. Peltate, capitate glandular and non-glandular trichomes were found on the stem, leaf, petiole, calyx and corolla surfaces of A. orientalis. Three sub-types of capitate glandular trichomes were found whereas two sub-types of non-glandular ones were stated on the several organs of A. orientalis. Glandular trichomes were mainly observed on calyx and corolla, but non-glandular ones were found on the stem, leaf surface and petiole. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19754 Bangladesh J. Bot. 43(1): 91-95, 2014 (June)